Ancient Judaism in its Hellenistic Context - Bakhos, Carol, (Supplements to the Journal for the Study of Judaism ;, 2004)
This volume explores the ways in which Jews lived within the Hellenistic and Greco-Roman contexts, how they negotiated their religious and social boundaries in their own distinctive manner. Scholars demonstrate how the Jewish encounter with Hellenism led not to a conscious struggle with alien forces but rather in many instances to an active re-tailoring and re-shaping of tradition in light of their material, ideological and philosophical surroundings. That is to say, the Jews, a minority people, maintained their identity by adapting the trappings, to varying degrees, of their milieu. These essays also reflect many issues that emerge when we study the development of several aspects of Jewish Civilization through the ages in light of broad socio-political, cultural and philosophical contexts.